2018
DOI: 10.1021/acsnano.7b07439
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Carbon Nanotubes Reduce Hypertrophic Scar via Regulating Cell Behavior

Abstract: Hypertrophic scars, characterized by excessive cell proliferation, disordered cell growth, and aberrant deposition of collagens, could cause significant clinical problems. Herein, aligned carbon nanotubes (ACNTs) were synthesized via chemical vapor deposition, and bulk ACNTs were pulled out from the arrays. The capacity of the ACNTs to reduce hypertrophic scar formation was evaluated both in vitro and in vivo. The results demonstrated that the ACNTs suppressed the overproliferation of fibroblast cells, directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 77 publications
2
42
1
Order By: Relevance
“…on December 6, 2020 http://advances.sciencemag.org/ Downloaded from of -SMA compared with random fibers groups (Fig. 5, C to E), consistent with previous studies showing that the orientated nanostructure could inhibit the expression level of -SMA and reduce scars (11,27). Our study also showed that the anisotropic electrospun fiber matrix could reduce the expression of -SMA and inhibit the differentiation of fibroblasts into myofibroblast phenotype.…”
Section: Phenotypic Differentiation and Ecm Reorganization Of Fibroblsupporting
confidence: 91%
See 1 more Smart Citation
“…on December 6, 2020 http://advances.sciencemag.org/ Downloaded from of -SMA compared with random fibers groups (Fig. 5, C to E), consistent with previous studies showing that the orientated nanostructure could inhibit the expression level of -SMA and reduce scars (11,27). Our study also showed that the anisotropic electrospun fiber matrix could reduce the expression of -SMA and inhibit the differentiation of fibroblasts into myofibroblast phenotype.…”
Section: Phenotypic Differentiation and Ecm Reorganization Of Fibroblsupporting
confidence: 91%
“…Cell morphology changes were believed to be highly associated with cell proliferation. Previous studies illustrated that topographical cues such as aligned nanogrooved substrate and carbon nanotubes could modulate cell shape and suppress fibroblast proliferation (27). On the other hand, studies have reported a significant synergistic stimulating effect on cell proliferation and differentiation from the topological and chemistry cues of bioscaffolds (35).…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of multi-walled carbon nanotubes (MCNTs) [ 19 ], one of the most representative nanomaterial, with unique electrical, mechanical, and surface properties, carbon-based nanotechnology has been rapidly developing as a platform technology for a variety of uses including biomedical applications, and up to now MCNTs appear well suited as biomaterials to enhance the properties and function of the medical devices, for example for improving tracking of cells, sensing of microenvironments, delivering of transfection agents and providing nanostructured surfaces for optimal integration with the host body [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ], which is not only because of their ability to simulate dimensions of proteins that comprise native tissue using their unique properties but also because of their higher reactivity for cell interactions to improve the cellular functions. Although MCNTs have not been examined as bone repair materials for a long time, there have been already a lot of related original publications.…”
Section: Introductionmentioning
confidence: 99%
“…According to the wall layer, it can be divided into single-walled CNTs (SWCNTs) and multi-walled CNTs (MWCNTs) (Figure 1). It is the most commercialized nanofiber with the highest strength and the smallest diameter [19][20][21]. Moreover, CNTs have good toughness, which can withstand 40% of tensile strain without brittle behavior or fracture phenomenon, thus improving the toughness of matrix composite [22].…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%